Quantum heat engine with long-range advantages. (1st March 2023) - Solfanelli, Andrea; Giachetti, Guido; Campisi, Michele; Ruffo, Stefano; Defenu, Nicolò
Abstract: Long-range interacting quantum devices provides a promising route for quantum technology applications. Here, the presence of long-range interactions is shown to enhance the performances of a quantum heat engine featuring a many-body working substance. We focus on the paradigmatic example of a Kitaev chain undergoing a quantum Otto cycle and show that a substantial thermodynamic advantage may be achieved as the range of the interactions among its constituents increases. The advantage is most significant for the realistic situation of a finite time cycle: the presence of long-range interactions reduces the non-adiabatic energy losses, by suppressing the detrimental effects of dynamically generated excitations. This effect allows mitigating the trade-off between power and efficiency, paving the way for a wide range of experimental and technological applications.